Análise filogenética da família multigênica Bet v 1 em Eucalyptus grandis - Miura, Natália Tamagusko [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The molecular characterization of a mutation in Eucalyptus grandis resulted in the development of a SCAR marker (Sequence Characterized Amplified Region) that showed identity with 19 regions in the genome, which downstream coding sequences multigene family proteins Bet v 1. These proteins are essential in plant defenses, because they promote resistance against pathogens through proteins synthesis induced by pathogenesis-related (PR), which features a mechanism known as hypersensitivity. Due the importance of these proteins in fighting against pathogens, as well as its relationship with the mutant E. grandis, this study aimed to perform phylogenetic analyzis of the genes in this multigene family E. grandis and among other plant species. In E. grandis were found 69 genes belonging to multigene family Bet v 1, while in the other species the number of genes varied from 1 to 35. The largest amount of PRs genes in E. grandis may confer an adaptive advantage with respect to fight against pathogens, since the multigene family Bet v 1 is in continuous process of duplication and mutation, ensuring a host-pathogen coevolution and supporting adaptability capacity. The gens of the multigene family found Bet v 1 were used to infer evolutionary history of this family by constructing trees of Maximum Likelihood among species and E. grandis. The Maximum Likelihood analyzis demonstrated that the evolutionary history of the multigene family Bet v 1 didn't follow the same evolutionary pattern as plant species, indicating the need for the inclusion of more conserved genes in the analysis. The phylogenetic representation in E. grandis reveals that the similarity of genes from the same region is higher compared to genes located in different regions, probably due to sucessive duplication and gene mutations that occurs through processes neofunctionalization and/or subfunctionalization. Since the oldest events are weakly supported phylogenetic ...

A caracterização molecular de uma mutação em Eucalyptus grandis resultou no desenvolvimento de um marcador SCAR (Sequence Characterized Amplified Region) que apresentou identidade com 19 regiões no genoma, que a jusante possuía sequências codificadoras de proteínas da família multigênica Bet v 1. Essas proteínas são essenciais na defesa das plantas, pois promovem resistências contra os patógenos através de sínteses de proteínas induzidas por pathogenesis-related (PR), o que caracteriza um mecanismo conhecido como hipersensibilidade. Dada a importância de tais proteínas no combate aos patógenos, assim como sua relação com o mutante de E. grandis, este trabalho teve como objetivo realizar análises filogenéticas dos genes dessa família multigênica em E. grandis e entre demais espécies vegetais. Em E. grandis foram encontrados 69 genes pertencentes à família multigênica Bet v 1, enquanto nas demais espécies o número de genes variou de 1 a 35. A maior quantidade de genes PRs em E. grandis pode conferir uma vantagem adaptativa com relação ao combate contra os patógenos, uma vez que a família multigênica Bet v 1 está em contínuo processo de duplicação e mutação, garantindo uma coevolução patógenohospedeiro e auxiliando na capacidade de adaptação. Os genes da família multigênica Bet v 1 encontrados, foram utilizados para inferir a história evolutiva dessa família através da construção de árvores de Máxima Verossimilhança entre espécies e em E. grandis. As análises de Máxima Verossimilhança demonstraram que a história evolutiva da família multigênica Bet v 1 não seguiu o mesmo padrão evolutivo que as espécies vegetais, indicando a necessidade da inclusão de genes mais conservados na análise. A representação filogenética em E. grandis revela que a similaridade dos genes de uma mesma região é maior em relação aos genes localizados em regiões ...
Keywords: Eucalyptus grandis - Resistência a doenças e pragas - Aspectos genéticos; Eucalipto - Filogenia; Plantas - Parasito; Proteinas - Analise; Genetica vegetal; Proteins Analysis